Recent Technological Advancements for Identifying and Exploiting Novel Sources of Pest and Disease Resistance for Peanut Improvement - Akshaya Kumar Biswal; Peggy Ozias-Akins; Carl Corley Holbrook (Agronomy)
Peanut, also known as groundnut (Arachis hypogaea L.), is an important oilseed and food crop globally, contributing significantly to the economy and food security. However, its productivity is often hampered by pests and diseases. Traditional breeding methods have been used to develop resistant cultivars, but these are often time-consuming and labor-intensive. Recent technological advancements have revolutionized the identification of novel resistance sources and the development of resistant peanut cultivars. This review explores the latest techniques and approaches used in peanut breeding for pest and disease resistance, focusing on the identification of resistance loci and their incorporation into peanut using marker-assisted selection (MAS) and genomic tools. Next-generation sequencing (NGS) technologies, bioinformatics pipelines, comparative genomics, and transcriptomics have helped identify a plethora of candidate genes involved in pest resistance. However, peanut lags behind other cereal crops in terms of phenomics and precision genetic techniques for their functional validation. In conclusion, recent technological advancements have significantly improved the efficiency and precision of peanut breeding for pest and disease resistance and hold great promise for developing durable and sustainable resistance in peanut cultivars, ultimately benefiting peanut farmers and consumers globally.